A Rare Case of Ovarian Filariasis in Abidjan - Doukouré Brahima; Abouna Alain Didier; Dou Gonat Serge Pacôme; Aman Nguiessan Alphonse; Koffi Abdoul; Diomandé Mohenou Isidore Jean-Marie (Case Reports in Pathology)
Ovarian filariasis is an exceptional disease and displays a major diagnostic problem even in endemic areas. We reported the case of a 19-year-old patient who had ovarian cyst which was revealed by chronic pelvic pain. The histological examination of oophorectomy specimen led to the Wuchereria bancrofti filariasis of the ovary. The anatomopathologic examination is required for the diagnosis of this disease.